Mariano Siskind, Cosmopolitan Desires: Global Modernity and World Literature in Latin America - Josiowicz, Alejandra (Prismas - Revista de historia intelectual, 2014)
Mariano Siskind, Cosmopolitan Desires: Global Modernity and World Literature in Latin America, Evanston, Northwestern University Press, 2014, 357 páginas